LEGAL ANALYSIS OF CONSTITUTIONAL COURT DECISION NUMBER 90/PUU-XXI/2023 AS A FORM OF EXPANSION OF POSITIVE LEGISLATOR AUTHORITY FROM THE PERSPECTIVE OF LEGAL JUSTICE - Ellydar Chaidir; Moza Dela Fudika; Puti Mayang Seruni (Jurnal Kajian Ilmu Hukum, 2025)
The Constitutional Court Decision No. 90/PUU-XXI/2023 concerning the age requirement for presidential and vice-presidential candidates has generated extensive constitutional debate in Indonesia. As the guardian of the 1945 Constitution, the Constitutional Court is expected to uphold legal certainty and constitutional consistency. However, this decision introduces a new interpretation by adding normative meaning to Article 169 letter q of Law No. 7 of 2017 on General Elections, raising questions regarding the limits of judicial authority. This article aims to analyze the ratio decidendi of Decision No. 90/PUU-XXI/2023 within the framework of open legal policy and to examine the extent to which the Constitutional Court has exercised its authority in adding legal norms. This study employs normative juridical research using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials. The findings indicate that the decision reflects a shift in the Constitutional Court’s role toward norm creation, which deviates from its function as a negative legislator and undermines legal certainty and the principle of justice.